Ex Vivo Normothermic Machine Perfusion Is Safe, Simple, and Reliable: Results From a Large Animal Model. (February 2015) - Nassar, Ahmed; Liu, Qiang; Farias, Kevin; D'Amico, Giuseppe; Tom, Cynthia; Grady, Patrick; Bennett, Ana; Diago Uso, Teresa; Eghtesad, Bijan; Kelly, Dympna; Fung, John; Abu-Elmagd, Kareem; et al.
Introduction . Normothermic machine perfusion (NMP) is an emerging preservation modality that holds the potential to prevent the injury associated with low temperature and to promote organ repair that follows ischemic cell damage. While several animal studies have showed its superiority over cold storage (CS), minimal studies in the literature have focused on safety, feasibility, and reliability of this technology, which represent key factors in its implementation into clinical practice. The aim of the present study is to report safety and performance data on NMP of DCD porcine livers. Materials and Methods . After 60 minutes of warm ischemia time, 20 pig livers were preserved using either NMP (n = 15; physiologic perfusion temperature) or CS group (n = 5) for a preservation time of 10 hours. Livers were then tested on a transplant simulation model for 24 hours. Machine safety was assessed by measuring system failure events, the ability to monitor perfusion parameters, sterility, and vessel integrity. The ability of the machine to preserve injured organs was assessed by liver function tests, hemodynamic parameters, and histology. Results . No system failures were recorded. Target hemodynamic parameters were easily achieved and vascular complications were not encountered. Liver function parameters as well as histology showed significant differences between the 2 groups, with NMP livers showing preserved liver function and histological architecture, while CS livers presenting postreperfusion parameters consistent with unrecoverable cell injury. Conclusion . Our study shows that NMP is safe, reliable, and provides superior graft preservation compared to CS in our DCD porcine model.